Pengaruh Pemanasan Berulang Media Nutrient Agar terhadap Hasil Uji ALT Bakteri Staphylococcus aureus dan Escherichia coli - Elisa Rinihapsari; Benaya Yamin Onesiforus; Salsa Aten Riya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Nutrient Agar is a universal medium containing agar, meat extract, yeast extract and peptone. NA media is often made in large quantities, stored under sterile conditions, and then reheated when needed. Repeated heating can reduce the number of bacterial colonies that grow because the components that make up the media become damaged. This study aimed to determine the effect of repeated heating of NA (Nutrient Agar) media 4 times on the Total Plate Count (TPC) test results for Staphylococcus aureus and Escherichia coli bacteria. The number of bacteria that grew on the media with varying amounts of heating was calculated, and the results showed that repeated heating 4 times caused a decrease in the number of bacterial colonies that grew on the NA media. The ANOVA test gave a value of p = 0.000 for the two types of bacteria separately, which showed that there is a significant difference between the number of bacteria in varying amounts of media heating. This research concluded that repeated heating of NA (Nutrient Agar) media affects the TPC test results for Staphylococcus aureus and Escherichia coli.